The Impact of Hate Speech on the Dakwah of the Tabligh Jamah on Social Media - Furqan; Hasan Sazali (Universitas Serambi Mekkah, 2024)
Social media is a means of spreading news from and to the wider community. However, this technological progress is not accompanied by wisdom in using it. Hate speech is often found, which is very dangerous and contradicts the teachings of Islam, which encourages its followers to always respect each other's creatures. This research aims to determine the impact of hate speech on the Tablighi Jama'ah’s preaching on social media. Researchers used a qualitative approach with a literature study. Data sources include reports, news, religious lectures, articles, and other documents relevant to the topic of this discussion. The data collection method was carried out through library research on writings related to hate speech from an Islamic perspective. The data analysis used is content analysis using an inductive and deductive approach. The result of the discussion is that hate speech is speech that violates religious rules. Because hate speech can hurt other people. Types of hate speech according to Islam are backbiting, lying, namimah, or provocation, and slander. The factors that cause hate speech to occur are internal and external factors. The principles that must be possessed in order to avoid hate speech behavior are honesty, fairness, accuracy, and straight motives. The solution is the need for cooperation from all parties, open discussion about clear boundaries between hate speech and freedom of speech, and a comprehensive and intensive view of human nature.